2019
DOI: 10.1002/jqs.3175
|View full text |Cite
|
Sign up to set email alerts
|

Middle to late Pleistocene record of explosive volcanic eruptions in marine sediments offshore Kamchatka (Meiji Rise, NW Pacific)

Abstract: This paper presents the first detailed study of a late Pleistocene marine tephra sequence from the NW Pacific, downwind from the Kamchatka volcanic arc. Sediment core SO201-2-40, located on the Meiji Rise~400 km offshore the peninsula, includes 25 tephras deposited within the last 215 ka. Volcanic glass from the tephras was characterized using single-shard electron microprobe analysis and laser ablation inductively coupled mass spectrometry. The age of tephras was derived from a new age model based on paleomag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(34 citation statements)
references
References 78 publications
(149 reference statements)
1
33
0
Order By: Relevance
“…The cases of compositionally identical products of different eruptions from the same volcanic center are also known. For example, Derkachev et al (2020) reported two late Pleistocene layers produced by large eruptions from Gorely caldera, which have barely distinguishable major and trace element composition of glass. On a longer timescale of 100 000 years, the products of the Gorely caldera eruptions are more variable (Seligman et al, 2014), enabling their identification using glass composition in tephra and welded tuffs.…”
Section: Using Composition Of Glasses For Fingerprinting Ash Layers Imentioning
confidence: 99%
See 1 more Smart Citation
“…The cases of compositionally identical products of different eruptions from the same volcanic center are also known. For example, Derkachev et al (2020) reported two late Pleistocene layers produced by large eruptions from Gorely caldera, which have barely distinguishable major and trace element composition of glass. On a longer timescale of 100 000 years, the products of the Gorely caldera eruptions are more variable (Seligman et al, 2014), enabling their identification using glass composition in tephra and welded tuffs.…”
Section: Using Composition Of Glasses For Fingerprinting Ash Layers Imentioning
confidence: 99%
“…In the Kamchatka volcanic arc, the Holocene tephrochronological framework (until recently) has been based mainly on direct tracing of tephra layers, bulk composition of tephra, and bracketing radiocarbon dates (e.g., Bazanova et al, 2005;Braitseva et al, 1998Braitseva et al, , 1996Braitseva et al, , 1995Braitseva et al, , 1997Pevzner, 2010;Pevzner et al, 1998Pevzner et al, , 2006. Significant progress towards creating geochemical database of Kamchatka tephras has been achieved in the past 10 years (Dirksen et al, 2011;Kyle et al, 2011;Plunkett et al, 2015;Ponomareva et al, 2013aPonomareva et al, , b, 2017Ponomareva et al, , 2015b. However, the published geochemical data are mostly restricted to the Holocene and do not include data on trace element composition of volcanic glasses.…”
Section: Introductionmentioning
confidence: 99%
“…(23) (15) South East Asia (Bouvet de la Maisonneuve and Bergal-Kuvikas (2020) (16) Aira caldera, Japan (Nishizawa and Suzuki, 2020) (17) Aso caldera, Japan (Miyabuchi and Sugiyama, 2020) (18) Lake Suigetsu, Japan (Maruyama et al, 2020) (19) Tohoku area, Japan (Suzuki et al, 2020) (20) Towada volcano, Japan (Ishimura and Hiramine, 2020) (21) Kamchatka Peninsula, Russia (Zelenin et al, 2020) (22) Meiji Rise, NW Pacific Ocean (Derkachev et al, 2020) (23) Auckland Volcanic Field, New Zealand (Peti et al, 2020) show that the eruptives can be distinguished using their glass geochemistry, thereby providing a key reference dataset to aid the identification of distal deposits.…”
Section: Theme 1: Tephrochronological Perspectivesmentioning
confidence: 99%
“…Nevertheless, reconstructing the pre-Holocene volcanic history is more complex as older sequences are rare and can be affected by erosion by glaciers and meltwater, or burial by subsequent eruptives. Derkachev et al (2020) address this issue within the final paper of the volume, by identifying and assessing pre-Holocene eruptives within a marine core retrieved from the Meiji Rise, northwest Pacific,~400 km downwind from the Kamchatkan volcanic arc, because marine records can provide the most complete and long-term tephra records for this period. Derkachev et al (2020) identify 25 tephras deposited within the past 215 ka.…”
Section: Theme 1: Tephrochronological Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation